URGENSI PEMBERIAN EDUKASI PRA NIKAH DAN ILMU PARENTING TERHADAP CALON SUAMI ISTRI PERSPEKTIF HUKUM ISLAM - Nerli Citra Lestary; Ridwan, Muh. Saleh; Mapuna, Hadi Daeng (Universitas Islam Negeri Alauddin Makassar, 2024)
Marriage is not only about biological needs, but also involves the parents of both parties, their siblings, even their respective families, and many other things that must be known in navigating the household ark, including the obligations and rights of the husband towards his wife, and vice versa. Apart from that, their obligations and rights will increase when they have children. As parents, it is their duty to provide for their children's needs, love, nurture, and assist their children in every development. For every prospective bride and groom, both prospective husbands and prospective wives must participate in pre-marital education, which discusses life in living a married life, starting from providing material related to husband and wife to discussing parent-child. It is very importantto know how the implementation and impact of providing pre-marital education and parenting knowledge. In this research, the field research method is used, with data collection techniques by means of interviews and documentation. Therefore, it is very important and influential for prospective brides who will become husband and wife to follow and accept the provision of pre-marriage education and parenting knowledge as provisions before living life after marriage, so every prospective bride is expected not to underestimate or underestimate one of these stages.